DIGITAL TECHNOLOGIES IN THE INTERIOR DESIGN OF CIVIL BUILDINGS - Кисиль, С. С.; Полякова, О. В.; Булгакова, Т. В. (Art and Design, 2020)
Research and identification of theoretical and practical possibilities of digital technologies use interior design of civil buildings. The material of the article is focused on shaping with the introduction of modern digital technologies in the interiors design of civil buildings. Methodology. The research is based on historical, cultural, artistic, stylistic, iconographic methods. Methods of comparative, typological analysis and experimental design were also used. Results. The modern trends in the use of digital technologies in the interiors design of civil buildings are revealed. Design approaches to the organization of object-spatial filling based on the analysis of foreign experience accumulated in recent years, by generalizing the use of digital technologies in the modern interior design enironment of civil buildings. Namely: the emphasis on artistic expressiveness and imagery and the dominance of the functional component in the solution of interactive objects. Each of these approaches is implemented through the use of digital hardware and different ways of incorporating them into the structure of the object-space environment. The study of numerous examples of civilian interiors has made it possible to establish that digital hardware is the leading in shaping the interactive space. Scientific novelty. It’s about exploring trends in the use of digital technologies in the process of creating interactive forms with their specific artistic elements in forming new aesthetic paradigms of contemprary interior design of civilian buildings. Practical significance. The results presented in this work – the latest technologies, tools and approaches to the formation of a spatial domain in conjunction with digital technologies can be used in the design process of interiors of civil buildings. The findings can be applied in the preparation of specialist designers in institutions of higher education in the artistic field.